Conformations of Calix[4]arenes. An Investigation Based on CSD Data. Part III. Calix[4]resorcinarenes - Klimentova, J.; Lukes, I.; Vojtisek, P. (Ye.A.Buketov Karaganda State University Publ., 2018)
In the first part of this investigation (Part I), cone conformers of calix[4]arenes with methylene and heteroatom bridges from the Cambridge Structural Database (CSD) were investigated, in the second part (Part II) we focused on structures of partial cone, 1,2-alternate and 1,3-alternate conformers with methylene- and heteroatom- bridged calix[4]arenes represented in this Part II. This, third part (Part III) of the review is a sequel and it is on conformations and geometry of calix[4]resorcinarenes scafolds, again using the data from the CSD. The results were compared to data of calix[4]arene structures in our previous work. The effects of substitutions and inter/intramolecular interactions present in the structure on the symmetry of the resorcinarene base frame were evaluated with the help of previously introduced stereochemical parameters α, β, and δ. Utilization of new, slightly modified scale of parameters α', β', δ' was tested, too. To sum up, these parameter are useful not only for describing the geometry of calix[4]arenes, but for calix[4]resorcinarenes, too. The calix[ 4]resorcinarenes seem to be more conformationally flexible and the «flat» arrangements are more favoured there. Generally, the substitution is more complex and more irregular in the case of calix[ 4]resorcinarenes, and it is relatively difficult to found some common patterns. However, as all these results were obtained from solid state data, no conclusion concerning conformations and behavior of these molecules in solution can be stated, similary as in the case of calix[4]arenes.
Каликс[4]арендердің конформациялары. CSD мəліметтеріне негізделген зерттеулер. III-бөлім. Каликс[4]резорцинарендер
Конформации каликс[4]аренов. Исследование, основанное на данных CSD. Часть III. Каликс[4]резорцинарены
Keywords: X-ray structures determination; Cambridge Structural Database (CSD); stereochemistry of calix[ 4]resorcinarenes; conformations; distorsion parameters; symmetry; substitution patterns; deformation of base frame